Penegakan Hukum Pemilu di Provinsi Gorontalo: Telaah Kritis terhadap Implementasi Undang-Undang Pemilu - Muin, Juliansyah; Ismail, Dian Ekawaty; Ahmad (RechtJiva, 2026)
This study examines the enforcement of election law against money politics in Gorontalo Province under Law Number 7 of 2017 on General Elections. Elections as an expression of popular sovereignty require fairness and integrity, yet in practice continue to be challenged by widespread money politics that undermines democratic values. This research employs a normative legal method with statutory and conceptual approaches, supported by secondary data and case illustrations derived from official reports of the Election Supervisory Body (Bawaslu). The findings indicate that although legal provisions on money politics are clearly regulated, their enforcement remains ineffective, as many cases fail to proceed to the judicial stage. This ineffectiveness is influenced by evidentiary difficulties, weak institutional coordination within the Integrated Law Enforcement Center (Gakkumdu), and a permissive legal culture toward transactional political practices.